Cerebrospinal fluid biomarkers in parkinsonian conditions: an update and future directions. Issue 10 (1st April 2014) - Magdalinou, Nadia; Lees, Andrew J; Zetterberg, Henrik
Abstract : Parkinsonian diseases comprise a heterogeneous group of neurodegenerative disorders, which show significant clinical and pathological overlap. Accurate diagnosis still largely relies on clinical acumen; pathological diagnosis remains the gold standard. There is an urgent need for biomarkers to diagnose parkinsonian disorders, particularly in the early stages when diagnosis is most difficult. In this review, several of the most promising cerebrospinal fluid candidate markers will be discussed. Their strengths and limitations will be considered together with future developments in the field.